Parents who lead : the leadership approach you need to parent with purpose, fuel your career, and create a richer life - Friedman, Stewart D.; Westring, Alyssa F. (Boston : Harvard Business Review Press, 2020)
"Drawing on the principles of his book Total Leadership--a national bestseller and popular program taught in organizations worldwide--Stewart Friedman and coauthor Alyssa Westring show working parents how to lead more purposeful lives, characterized by harmony, connection, and impact. Being a parent can be a disorienting experience filled with disruptive transitions, constant pushes and pulls at work, at home, and in the community, endless to-do lists, and identity crises. It's easy to lose track of who you are and what really matters most when you're balancing so much at once. It doesn't have to be this way. As a parent, you can harness the power of leadership principles and discover how to thrive in all aspects of your life. Drawing on their experience as researchers, educators, consultants, coaches, and parents, Friedman and Westring offer a robust and proven method--designed specifically for parents--that will help you gain a greater sense of purpose and control. This method includes: Designing a future based on your core values, engaging with your children in meaningful ways, cultivating a community of caregiving and support, in all parts of your life, experimenting to discover better ways to live and work. Powerful, practical, and indispensable, Parents Who Lead is the guide you need to forge a better future, foster meaningful and mutually rewarding relationships, and design sustainable solutions for creating a richer life for yourself, your children, and your world"--
The leadership challenge of your life: Parent with purpose, fuel your career, and create a richer life -- Get started -- Find the right support -- Your partnership. Envision your future together: Value values -- Craft a collective vision -- Picture tomorrow -- Embrace the four-way view: Examine the four domains -- Notice how the strands weave -- Overcome inhibitions to creative thinking -- Explore both of your four-way views -- Take the leadership leap -- Your world. Engage your children: See parenting in view of your whole life -- Know what children need -- Get on the same page about your children's needs -- Discover your children anew -- Connect with colleagues: Navigate relationships with bosses -- Send the right message to your direct reports -- Find support among coworkers -- Reach further out -- Cultivate your community: Define friends and neighbors -- Honor childcare providers and teachers -- Seek out members of community organizations -- Take in extended family -- Your evolution. Try a new way: Think like a change agent -- Pursue family four-way wins -- Collaborate in creating change -- See yourselves differently: Grow as a family -- Teach each other -- Welcome surprises.
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3
Keywords: Parenting; Leadership; Work and family; Work-life balance; Leadership; Parenting; Work and family; Work-life balance; elektronické knihy; electronic books